Valuation of Photovoltaic Projects in The Development Phase Using the Modified Option Method - Tomasz LUKASZEWSKI (Communications of International Proceedings, 2023)
The motivation for conducting a study on the valuation of projects in the development phase using a modified option method was the need to test the prevailing view in the literature that the cash flows that a project would generate during the operating period are best used as the value of the underlying asset in an option model. The article verifies this view, shows its flaws and proposes an alternative solution of replacing the project's "operating" value with a "development" value. As a method, a binomial valuation model was used to estimate the value of a compound option. The article concludes that when valuing a photovoltaic project in the development phase in Poland using the option method, it is advisable to replace the operating value parameter in the valuation model with the price that an investor could obtain by selling the project. As shown, such a modification gives more reliable results, allows to refer to observable market values and facilitates the interpretation of the obtained results by relating them to the actual economic parameters of the project. The publication aims to improve the method to make it more understandable and widespread as a practical tool for investment planning.
Keywords: photovoltaic projects; projects development; real options